Uji Toleransi Dua Kultivar Kedelei (Glycine max L.) Terhadap Cekaman Kekeringan dan Pengaruhnya Terhadap Komponen Hasil - Sumbari, Chika; Ernanda, Revi (Journal Galung Tropika, 2021)
The increasing population and the demand for soybean consumption in Indonesia are not comparable to soybean production, which is still low. Land conversion and changes in climate patterns that cause drought stress are also triggers for low production. Drought stress can be anticipated by using drought stress-tolerant cultivars at various growth phases. This study aimed to determine the effect of drought stress on yields and yield components of several soybean cultivars. In addition, to determine the soybean cultivars that are most resistant to drought stress. This study was arranged experimentally using a factorial (3x2) split-plot design. The main plot, namely drought stress, consisted of three levels: watering once a day, once every three days, and watering once every six days. The sub-plots were soybean cultivars with three replications consisting of 2 levels, namely Wilis and Anjasmoro cultivars. The selection of these 2 cultivars was made on purpose because farmers had easy access to seeds. Determination of drought stress-resistant cultivars using the stress tolerance index (ITC). Drought stress caused almost all yield and yield component variables to decrease, such as the number of pods, the number of seeds per pod, and the total weight of seeds. Based on the stress tolerance index (ITC), it is known that the Wilis cultivar is more tolerant to drought stress than the Anjasmoro cultivar.